The Neuroeconomics of Distrust: Sex Differences in Behavior and Physiology - Zak, Paul J; Borja, Karla; Matzner, William T; Kurzban, Robert (American Economic Review, 2005)
The Neuroeconomics of Distrust: Sex Differences in Behavior and Physiology by Paul J. Zak, Karla Borja, William T. Matzner and Robert Kurzban. Published in volume 95, issue 2, pages 360-363 of American Economic Review, May 2005